(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD) affects 15 to 40% of people in Western nations, 9 to 40% of people in Asian countries and 6-35% global incidence in Western industrialized countries.1,2 Objective: To compare ultrasound and computed tomography findings in non-alcoholic fatty liver disease in obese and non-obese cases. Methods: A cross sectional analytical study was conducted at DHQ Hospital Narowal. 270 patients of both genders with ages 13 and 95 years who had a fatty liver on ultrasound and are non-alcoholics were included in this study. Patients with any other liver abnormality and having history of alcohol intake were excluded. The variables of age, height, weight, gender and BMI were recorded. Patients were categorized in two groups obese and non-obese on basis of BMI. Grading of fatty liver on ultrasound and CT scan were noted down on a predesigned data collection sheet. Results: Out of 270 patients of NAFLD, 55.9% were females and 44.10% were males while 74.44% subjects were obese 25.55% were non obese. The correlation between USG and CT findings was significant(r = 0.761 for non-obese and 0.868 for obese patients). Among obese cases of NAFLD grade I was the commonest, and lowest number of patients were of grade III. Among non-obese cases grade II was commonest. Conclusion: There is a good correlation between the structural ultrasound criteria and CT criteria for diagnosis of nonalcoholic fatty liver disease. This disease is seen more commonly in obese individuals and is more common in females as compared to males.